Media planning in the promotional industries - Gerstman, Victoria C. (2019)
Media planning agencies occupy an interesting space within the promotional industries, at once part of and separate to advertising and media production. The ostensible role of media planning is to select the best media opportunities for conveying promotional messaging to a client brand’s desired target. The work of media planning, however, is characterised by fluxing media industrial conditions and shifting agency remits. This project therefore focuses on media planning as a distinct area of research, answering the question, ‘what is the role and the work of media planning as a sector?’